Diverse People in Diverse Businesses: Creating an Ecosystem around Inclusiveness - Vasilopoulos, Eleftherios Foivos (HAPSc Policy Briefs Series, 2022)
In Greece only one out of three people with difficulties in basic activities is employed (Eurostat, 2011). These significantly low employment rates among people with disabilities (PwDs) have negative implications regarding their living standards, making them economically dependent on social benefits and socially excluded. One of the main factors for that issue is the deficient rates of absorption of PwDs in the private sector, although multiple EU and Greek policies for the increase of these rates currently exist. This policy brief emphasizes on the existing situation, the reasons why disabled people are excluded from the private labor market and the potential of investing in all-inclusive work-systems for businesses. Finally, it provides policy recommendations, on both European and national level, for motivating enterprises to increase diversity in their workforce, through the creation of an EU Disability Inclusion Index and Regional Disability Projects.